2008
DOI: 10.1039/b716356h
|View full text |Cite
|
Sign up to set email alerts
|

Binding of protoberberine alkaloid coralyne with double stranded poly(A): a biophysical study

Abstract: Recognition of double stranded ribonucleic acid is a critical event in many biological pathways such as trafficking, editing and maturation of mRNA, interferon antiviral response and RNA interference. In the context of probing double stranded RNA binding small molecules, the interaction of the antitumor protoberberine alkaloid coralyne with double stranded poly(A) has been studied by various biophysical techniques. Typical hypochromic and bathochromic shifts in the absorption spectrum and appreciable quenching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 56 publications
(59 reference statements)
0
36
0
Order By: Relevance
“…To elucidate this problem further, the binding reactions between RNA and flavonoids in an aqueous phase were studied using ITC. ITC is an important tool for measuring the thermodynamics of interactions between small molecules and biopolymers, in which all binding parameters (n, K, ΔH and ΔS) are simultaneously determined in a single ITC experiment, thus obtaining information that cannot be obtained by other methods [35][37]. In our research, analysis of the ITC measurements revealed two interactions to be primarily enthalpy driven.…”
Section: Discussionmentioning
confidence: 67%
“…To elucidate this problem further, the binding reactions between RNA and flavonoids in an aqueous phase were studied using ITC. ITC is an important tool for measuring the thermodynamics of interactions between small molecules and biopolymers, in which all binding parameters (n, K, ΔH and ΔS) are simultaneously determined in a single ITC experiment, thus obtaining information that cannot be obtained by other methods [35][37]. In our research, analysis of the ITC measurements revealed two interactions to be primarily enthalpy driven.…”
Section: Discussionmentioning
confidence: 67%
“…The absorption spectral titrations were performed under stirring at 20 ± 0.5°C on a Jasco V660 unit (Jasco International Co. Ltd., Tokyo, Japan) equipped with a thermoelectrically controlled cell holder and temperature controller in matched quartz cells of 1 cm path length, following generally the methods standardized in our laboratory and described earlier [25,26,41].…”
Section: Absorption Titration Experimentsmentioning
confidence: 99%
“…It is also noteworthy that polyriboadenylic acid has the unique characteristic to exist in single stranded helical structure and parallel stranded double helix [33][34][35], the later being stabilized by base paired protonated adenines. Furthermore, many small molecules, particularly alkaloids, have been shown to induce unique self-structure in poly(A), the mechanism of which is still obscure [8,9,25,26,36,37]. Apparently, molecules that could induce self-structure in poly(A) may be useful as potential lead compounds for controlling the poly(A) chain elongation and mRNA degradation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Double stranded RNAs such as viral RNAs or siRNAs can trigger RNA interference in eukaryotes as well as interferon response in vertebrates [14][15][16]. This form of RNA is formed in cells through intra-and intermolecular RNA interactions and is involved in a range of biological processes [17]. A major event for a number of cellular pathways, such as trafficking, editing, maturation of cellular RNA, the interferon antiviral response and RNA silencing is the molecular recognition of ds RNA.…”
Section: Introductionmentioning
confidence: 99%